Merchants of culture : the publishing business in the twenty-first century - Thompson, John B. (John Brookshire) (Cambridge, UK : Polity, 2010)
'These are turbulent times in the world of book publishing. For nearly five centuries the methods and practices of book publishing remained largely unchanged, but at the dawn of the twenty-first century the industry finds itself faced with perhaps the greatest challenges since Gutenberg. A combination of economic pressures and technological change is forcing publishers to alter their practices and think hard about the future of books in the digital age.''In this book {u0D28}e first major study of trade publishing for more than thirty years - Thompson situates the current challenges facing the industry in a historical context, analysing the transformation of trade publishing in the United States and Britain since the 1960's. He gives a detailed account of how the world of trade publishing really works, dissecting the roles of publishers, agents and booksellers and showing how their practices are shaped by a field that has a distinctive structure and dynamic. By reconstructing this dynamic he is able to shed fresh light on how bestsellers are made and on why many thousands of books and authors find themselves marooned in an industry increasingly focused on short-term growth and profitability. Against this backcloth Thompson analyses the impact of the digital revolution on book publishing and examines the pressures {u08AF}th economic and technological {u0D28}at are re-shaping the field of trade publishing today.''The outcome of nearly five years of research, this major new book will establish itself as an exemplary work in the study of contemporary culture and will be essential reading for anyone interested in books and their future.'--BOOK JACKET.
Includes bibliographical references (p. 416-420) and index.
Keywords: Publishers and publishing -- United Kingdom -- History; Publishers and publishing -- United States -- History; Publishers and publishing -- Technological innovations; Booksellers and bookselling -- United Kingdom; Booksellers and bookselling -- United States; Literary agents -- United Kingdom; Literary agents -- United States